Mapping the progressive geologic history at the junction of the Alpine Mountain Belt and the Western Mediterranean Ocean - Gosso, Guido; Lardeaux, Jean-Marc; Zanoni, Davide; Volante, Silvia; Corsini, Michel; Bersezio, Riccardo; Mascle, Jean; Spaggiari, Luca; Spalla, Maria Iole; Zucali, Michele; Giannerini, Gérard; Camera, Laurent (Ofioliti, 2019)
This contribution illustrates a new type of map, the “geological event map” (1:250,000 scale), which highlights the progressive steps of the geologic history recorded in the polycyclic orogenic belt of the European Alps, at their southwestern termination facing the western Mediterranean Sea. The formula of historical progression simplifies comprehension of significant phenomenal visions and reorients public curiosity towards geologic processes. This part of the Alpine belt records a geologic history starting with the Variscan convergence during Devonian, throughout the opening of the Tethys Ocean, Alpine convergence, followed by Apennine subduction driving the opening of the Ligurian-Provençal Ocean. Finally, from late Miocene to Present a progressive tectonic inversion characterizes the Ligurian-Provençal continental margin. This geologic history, over a time period of 400 million years, which includes three successive Wilson Cycles, is displayed in 8 plates composed of maps and illustrations. Each map explains the effects of successive tectonic events by adding geologic changes that modify the petrogenetic and structural configurations. The last plate shows the finite state of the geologic history at present-time. The map legend is based on ten major geodynamic events of which rock associations, and their genetic environment, are described in simple divulgation terms, to stimulate interest of neophytes. Illustration of the evolution of rocks and structures side of each map aims at conveying to non specialists in tectonics and petrology the impact of mechanisms associated with the Earth’s deep engine upon surface changes.